Dysfunction of the Hypothalamic-Pituitary-Adrenal Axis in Opioid Dependent Subjects: Effects of Acute and Protracted Abstinence - Zhang, Guo-Fu; Ren, Yan-Ping; Sheng, Li-Xia; Chi, Yong; Du, Wan-Jun; Guo, Song; Jiang, Zuo-Ning; Xiao, Le; Luo, Xiao-Nian; Tang, Yi-Lang; Smith, Alicia K.; Liu, Zhen-Qi; et al. (The American journal of drug and alcohol abuse, 2008)
Objectives: The function of the Hypothalamic-Pituitary-Adrenal (HPA) axis during opioid dependence has been inconsistent. We compared HPA axis measures between subjects during methadone stabilization and drug-free detoxification with healthy controls. Methods: Sixty heroin dependent patients received either non-opiate treatment (NOT) with benzodiazepines and clonidine (n = 30) or methadone stabilization treatment (MT, n = 30), and their serum levels of corticotropin releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and cortisol (COR) were measured and compared to those of healthy, nondependent controls. Results: Compared with healthy controls, CRH was significantly lower (p <. 001) while COR was higher (p <. 001) during acute withdrawal in the NOT group. CRH and COR was lower (p <. 001), while ACTH was normal in the MT group compared to healthy controls. Conclusions: Our findings suggest that chronic opioid dependence may cause reduced function of the HPA axis, while opioid withdrawal may decrease the response of the pituitary to CRH and increase the adrenal response to ACTH.